PROMOSI KESEHATAN TENTANG CARA MEMBUANG OBAT YANG RUSAK ATAU KADALUWARSA DI RUMAHPUSKESMAS SUNGAI ULIN KOTA BANJARBARU - Melda; Samsul Hadi; Henny Maryani; Nazhipah Isnani; Hayatun Izma; Siti Malahayati; Hema Novita Redanti; Lukman Mahdi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Damaged drugs, leftover drugs in poor condition, and expired drugs that are not destroyed with the right method can cause environmental damage and clinical losses in the form of side effects due to using drugs that are no longer suitable for use. The purpose of this health promotion activity is to increase public knowledge about how to dispose of damaged or expired drugs at home. The health promotion methods used are leaflets and banners plus lectures or direct explanations to the public. Participants in this activity numbered 31 people, namely mothers who attended morning exercises held at the Sungai Ulin Health Center. The result of this health promotion is that the public becomes more aware of how to dispose of damaged or expired drugs at home properly